How to use Z-transforms to derive formula for Fibonacci seq?

You start with the fibonacci seq: ysub1 = 1 ysub2 = 1 ysub3 = ysub1+ysub2 then you reformulate this in terms of its z-transforms (these are the discrete versions of Laplace transforms). You then work out the z-transform representation of the nth term of the sequence. Then you perform an inverse z-tranform... show more You start with the fibonacci seq:
ysub1 = 1
ysub2 = 1
ysub3 = ysub1+ysub2
then you reformulate this in terms of its z-transforms (these are the discrete versions of Laplace transforms).
You then work out the z-transform representation of the nth term of the sequence.
Then you perform an inverse z-tranform to get the generalized ysubn = <some formula with sqrt(5) in it>

I saw this done once. Really really cool. I just cannot seem to get started on it again. Any pointers out there from some 3rd year electrical engineer freshly through a course in digital signal processing?

Thanks for any pointers.
1 answer 1